2022
DOI: 10.3389/fpubh.2021.818520
|View full text |Cite
|
Sign up to set email alerts
|

Face Masks Use and Its Role in Restraining the Spread of COVID-19 Pandemic in Saudi Arabia: Knowledge, Attitude, and Practices Based Cross-Sectional Study

Abstract: Face masks (FM) play a role in limiting the spread of viral infections; despite this, their role is influenced by the population's adherence to wearing the FM. However, the impact on the effectiveness of the FM is variable in various communities. This study aimed to investigate the knowledge, attitude, and practices toward FM use during COVID-19 in Saudi Arabia. This observational “cross-sectional questionnaire-based study was conducted in the Department of Physiology, College of Medicine, King Saud University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…These findings are consistent with those of studies conducted in China and Saudi Arabia, which also show a high level of positive attitude among participants. 43 , 44 The results in this study are also consistent with those of a study conducted in Saudi Arabia in which most participants had a positive attitude toward effective control of the pandemic by compliance with wearing of face masks. 28 High income was also associated with positive attitudes regarding wearing masks to reduce the chance of infection.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with those of studies conducted in China and Saudi Arabia, which also show a high level of positive attitude among participants. 43 , 44 The results in this study are also consistent with those of a study conducted in Saudi Arabia in which most participants had a positive attitude toward effective control of the pandemic by compliance with wearing of face masks. 28 High income was also associated with positive attitudes regarding wearing masks to reduce the chance of infection.…”
Section: Discussionsupporting
confidence: 89%
“…Steps are also required to ensure that the procedures and actions introduced by the college extend to all students. Meo/ Jan 2022 116 Face Masks Use and Its Role in Restraining the Spread of COVID-19 Pandemic in Saudi Arabia: Knowledge, Attitude, and Practices Based Cross-Sectional Study. 1356, respondents Online questionnaire on social media Saudi citizens have above-average knowledge/optimistic attitudes toward using face masks during the COVID-19 pandemic Hagag/Jan 2022 117 Exploration of Community Care Awareness about COVID-19 Sterilization.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“… 7 In Saudi Arabia, around 40% of the participants revealed that they would not wear masks if there were no financial ramifications imposed by the government. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 11 In addition, a cross-sectional study investigating the knowledge, attitude, and practices of face mask-wearing reported that most Saudi citizens had sufficient knowledge and a positive attitude toward consistently using face masks. 8 However, the study design refrained from extracting information regarding the degree of knowledge and demonstrated practices of the participants when using their face masks. 8 …”
Section: Introductionmentioning
confidence: 99%